The design of the roof of a mosque and how it affects thermal comfort / Mohamed Danial Sharom and Izzat Anuar - Sharom, Mohamed Danial; Anuar, Izzat (2018)
The inconsistent temperature in Malaysia affects the surrounding and comfort of people. For mosques the thermal comfort and the design strategies for the roof and openings are very important for their conduciveness. The aim of this research is to investigate the relationship between the roof of a mosque and its thermal comfort within its interior. Does the roof really affect the temperature of a mosque? In order to find the truth a few methods were used. Firstly, questionnaires were distributed to the users and secondly, observations were made inside the mosque. The expected result is that the roof plays a vital role in the thermal comfort of the mosque.